Computers without borders - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The increasing demand for information technology (IT) by organisations in the South might be partly met through a low-cost solution. Computer Aid, established in 1999, recycles used computing and IT equipment. Thousands of PCs, printers, and modems...